Netload-constrained Unit Commitment Considering Increasing Renewable Energy Penetration Levels: Impact of Generation Schedules and Operational Cost - Saleh Y. Abujarad; M. W. Mustafa; J. J. Jamian; Abdirahman M. Abdilahi; N. Zareen (International Journal of Applied Power Engineering (IJAPE), 2018)
In the context of low carbon power systems, the penetration levels of Renewable Energy Sources (RES) are expected to increase dramatically. In this regard, this paper investigates the maximum RES penetration level constrained by net load while considering an inflexible Unit Commitment (UC) model. To solve the UC problem, an enhanced priority list (EPL) based method is developed. In the proposed method, the plants were activated sequentially based on the operational price. The system constraint violations were repeatedly corrected until all system constraints (such as net load and spinning reserves) were satisfied. The proposed EPL method was efficient to achieve a near optimal solution under high shares of RES. Furthermore, the research work investigates three different scenarios representing penetration levels of 10% solar-only, 14.5% wind-only and 27.5% mixture of both solar and wind. The impact of each penetration level on the system scheduling and operational cost were analyzed in detail. The analysis presented shows that a potential operational cost savings of 21.6 $/MW, 20 $/MW and 11.1 $/MW is feasible under each of the represented scenarios, respectively.